ECHINOCOCCOSIS OF THE KIDNEY IN CHILDREN (BRIEF REVIEW OF THE LITERATURE) - N.N, Nazarov; E.A, Yakubov (PT. Antis International Publisher, 2025)
Objective: This study aims to provide a comprehensive review of hepatic echinococcosis in pediatric patients, focusing on diagnostic modalities, surgical treatment options, and associated complications. Method: A literature-based analysis was conducted, evaluating current clinical practices, imaging techniques, surgical approaches—including open and minimally invasive procedures—and adjunct pharmacological therapies. Results: The review highlights the central role of precise imaging and serological testing in early diagnosis. Surgical strategies should be tailored to cyst characteristics, with open surgery remaining crucial for complex cases. Minimally invasive techniques, while promising, require refinement to match the effectiveness of conventional approaches. Antiparasitic chemotherapy serves as a supportive measure in select patients. Recurrence is primarily linked to the thoroughness of surgical intervention rather than the choice of technique. Novelty: This study underscores the clinical relevance of emerging technologies such as laser devitalization and addresses ongoing controversies in the classification of surgical methods. It offers a nuanced evaluation of echinococcectomy in children, contributing to a better understanding of optimizing treatment outcomes and minimizing recurrence.